Bibliometric Analysis: Ice Breaking Techniques in Elementary Schools - Ramanda, Dea Maissy; Hidayah, Nurul; Yanti, Yuli (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study, an extensive bibliometric analysis, was conducted to detect trends, collaboration patterns, and topic structures in the scientific literature on primary school icebreaking approaches. Scientific publication data was acquired from Google Scholar using relevant keywords. The investigation covered 2021–2025 article documents. This study used VOSviewer for mapping and visualization. Annual publication patterns, mapping author, institution, and country collaborations, and keyword co-occurrence analysis to identify dominating research subject clusters and emergent issues were examined. The finding indicated that from 2021 to 2025, 83 research articles examined elementary school icebreaking approaches. VOSviewer's visual map also identified three main thematic clusters: Cluster 1 (elementary schools, ice-breaking implementation and benefits, and the effect of ice-breaking implementation, assisted by ice-breaking, on learning interest), Cluster 2 (elementary schools, learning, the role of ice-breaking, and ice-breaking techniques), and Cluster 3 (ice, ice-breaking, and mathematics learning). This cluster discusses public elementary school icebreaking methods, roles, and implementation. The network visualization showed that icebreaking was the most explored topic. The density visualization term with the brightest color and greatest diameter is "ice breaking," indicating that journals commonly study this topic. Overlay visualizations and studies on primary school icebreaking procedures showed changes from 2021 to 2025. This topic saw a rise in research in 2021-2023 but a sharp fall in 2024-2025. Finally, this bibliometric analysis presents a clear and structured summary of elementary school icebreaking research, indicating underexplored subareas and prospective study goals. These findings help academics, practitioners, and policymakers construct evidence-based educational approaches.